How positioning strategies affect co-branding outcomes - Hilary Wason; Nathalie Charlton (Cogent Business & Management, 2015)
Co-branding is a widely applied strategy, with research indicating differential benefits to the parent brands. Past studies suggest the source of these differences may be due to the partners' relative market position, and characteristics such as brand familiarity, brand equity and proximity to the consumer have been explored. However, the role of brand positioning has received little attention in the context of co-branding. The current study attempts to address this gap, considering the positioning of a brand and the impact of a co-branding strategy on customer perceptions. Using the Blankson and Kalafatis positioning typology, we explore the impact of co-branding on the parent brand perceptions from a hedonic vs. functional (utilitarian) focus. The results suggest that for hedonically oriented positioning strategies, fit between the brands is more important than fit between the product categories in driving positive brand perceptions. For a functionally oriented positioning strategy, the reverse holds, with product fit a more important factor than brand fit in driving post-alliance perceptions.
Keywords: 650